Pengaruh Reward dan Motivasi Kerja terhadap Kinerja Pegawai pada Kantor Kecamatan Pondok Aren Kota Tangerang Selatan - Ramadhan Reza Ilham; Raden Yeti Sumiaty (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to determine the effect of reward and work motivation on employee performance at the Pondok Aren Subdistrict Office, South Tangerang City. Using a quantitative method with 65 respondents, data analysis was conducted through a series of statistical tests, including validity and reliability tests, classical assumptions, multiple linear regression, correlation, coefficient of determination, and hypothesis testing. The results of the multiple regression analysis show the equation Y = 7.029 + 0.342X1 + 0.530X2, with a simultaneous correlation value of 0.874, indicating a very strong relationship. The coefficient of determination is 76.4%, meaning that 23.6% of employee performance is influenced by other factors not included in this study. Based on partial t-tests, reward was found to significantly affect employee performance with a t-value of 10.777 > t-table 1.998 and a significance level of 0.001 < 0.05. Work motivation also significantly affects employee performance with a t-value of 12.658 > t-table 1.998 and a significance level of 0.001 < 0.05. The results of the simultaneous f-test support this finding with an f-value of 100.539 > f-table 3.15 and a significance level of 0.001 < 0.05. In conclusion, reward and work motivation have a positive and significant effect on employee performance at the Pondok Aren Subdistrict Office.